Competitiveness Analysis and The Impact of Government Policies on Feed Maize Farming in Tanah Datar District - Hidayani, Sri Vina; Tanjung, Faidil; Khairati, Rusda (PINISI Discretion Review, 2024)
Maize ia an important food crop after rice and one of the commodities widely grown by farmers and a leading commodity in Tanah Datar. This research aims to analyze the competitiveness of corn farming in Tanah Datar Regency through comparative and competitive advantages, as well as to analyze the impact of government policies on corn farming in Tanah Datar Regency. The method used in this research is the survey method. The power analysis employed in this study is quantitative, using the Policy Analysis Matrix as a measurement tool. (PAM). The research results show that corn farming in Tanah Datar Regency is profitable both financially and economically. This shows a private profit of Rp 4,273,753 and a social profit of Rp 2,025,189. Corn cultivation in Tanah Datar Regency has competitive and comparative advantages. This can be seen from the PCR value of 0.50 and DRCR of 0.54 < 1, which means that corn farming has a high competitive advantage and comparative advantage. The impact of government policy shows that there are government policies that protect the prices of tradable outputs and inputs in the form of subsidized fertilizers. This is indicated by the Nominal Protection Coefficient for corn output of 1.2; the Nominal Protection Coefficient for inputs of 0.63; the Effective Protection Coefficient of 1.76; the Profitability Coefficient of 2.12; and the Subsidy Ratio to Producers of 0.64.